METHAPOR EXPRESSIONS IN “WHEN WE ALL FALL ASSLEEP WHERE DO WE GO” ALBUM BY BILLIE EILLISH - Adi, Soni Rahayu; Devita, Afni Apriliyanti (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2024)
Using metaphors in song lyrics could enrich aesthetic values and deep meaning to the listeners. This study aims to examine the kinds of metaphor expressions and the meaning contained in the lyrics of Billie Eilish's “When We All Fall Asleep Where Do We Go” album (2019) using the theory from Lakoff and Johson (2003) for metaphor types and Leech (1981) for the metaphor functions. The researcher used a descriptive qualitative method to conduct this research. The data collection is carried out through observation and note-taking techniques to record the metaphors in the album. It is found that there are 3 types of metaphor expressions as follows: Ontological, Structural, and Orientational. The type of figurative language most commonly used in this album is structural. Furthermore, there are six meanings of metaphor found in this album, as follows: Expressive, Directive, Informative, Aesthetic, Descriptive, and Phatic. The meaning metaphor commonly found in this album is Expressive.